PENGARUH SERVICE QUALITY DAN CUSTOMER SATISFACTION TERHADAP WORD OF MOUTH DALAM UPAYA PENINGKATAN JUMLAH MAHASISWA BARU DI AMIK AL MA’SOEM JATINANGOR - Rakhman, Faisal (STIBANKS Al Ma'soem Bandung, 2017)
This research aimed to analyze the influence of service quality and customer satisfaction on the word of mouth communication in an effort to increase the number of new students in AMIK Al Ma'soem Jatinangor using a model SerQual consisting of five dimensions. This research uses descriptive quantitative method. The research data was obtained from primary data by distributing questionnaires to students in AMIK Al Ma'soem and then processed with SPSS.The results showed that correlation is weak and there are not significant quality of service and customer satisfaction on the word of mouth communication in an effort to increase the number of new students in AMIK Al Ma'soem Jatinangor. F test results showed that the factors of service quality and customer satisfaction does not significant affect the word of mouth communication student AMIK Al Ma'soem Jatinangor to other people / prospective students.The R-square value obtained amounted to 0.102, or 10.2%, that meaning simultaneous service quality and customer satisfaction just contributes 10.2% to the effect on the word of mouth communication in AMIK Al Ma'soem Jatinangor students, while the rest (1-R²) of 89.8% is the amount of contributions made by other factors not examined.The study reveals that students expect comfortable classrooms, in other words clean, airy, and neatly arranged. Students also expect an increase in speed over the handling of complaints that arise and of course accompanied by appropriate solutions. And the management of AMIK Al Ma'soem Jatinangor must be improve and focus on other factors that allegedly could affect the number of new students who enroll, such as brand image, price and promotion.